Woody Species Colonization along Edge-Interior Gradients of Deciduous Forest Remnants in the Mae Khum Mee Watershed, Northern Thailand - Lamthai Asanok; Rungrawee Taweesuk; Nitpavaridsa Papakjan (International Journal of Forestry Research)
This study investigated the environmental factors and tree species characteristics that are important for the colonization of edge-interior gradients, for later application to the restoration of edge-transition areas created by highland agriculture in deciduous forests in the Mae Khum Mee watershed, northwest Thailand. Three belt plots (100 × 10 m) were established at the transition from the forest edge to the interior of two deciduous forest types (mixed deciduous forest [MDF] and deciduous dipterocarp forest [DDF]), for a total of six belt plots. The species composition of canopy trees and regenerated seedlings and saplings was assessed, together with several environmental factors. We analyzed the relative importance of the physical environment and recruitment limitation was evaluated in relation to the regeneration traits of tree species. The results indicated that it was difficult for DDF and MDF species to effectively colonize the near-edge areas of the forests, primarily because the key factors related to seedling and sapling colonization (i.e., recruitment limitation, the physical environment, and factors related to forest structure) did not match the edge environment. Generalist species experienced much less recruitment limitation along the edge-interior gradients of both DDFs and MDFs. Generalists such as Pterocarpus macrocarpus, Dalbergia cultrata, and Vitex pinnata exhibited more successful establishment under conditions at the edges of both deciduous forests. These findings suggest that the natural regeneration of generalist species can be utilized as a first step in forest-edge restoration due to their facilitation of subsequent colonization by primary forest species.